Requested Information in School Visits Schedule on Brazilian Museum Websites - Paiva, Victor Hugo Ferreira; Silva, Bruno Santana da (Informação em Pauta, 2023)
Museums can contribute to teaching-learning processes of their audiences, especially when they collaborate with educational institutions that work in formal education. Scheduling school visits to museums is a museum management activity that can serve as a starting point for this collaboration between museums and schools in promoting learning. However, few previous works have investigated the scheduling of school visits to museums. In this context, this work investigated the information requested in the scheduling of school visits on websites of 12 Brazilian museums through the content analysis method. 45 pieces of information were identified about responsible, institution, visitor group and visits. Of these, 21 of them were recurrent in at least three different museums. The information identified in this work can serve as a basis for future development and improvement of information systems to support museum management, in particular the digital ones, in order to favor communication and collaboration between museums and schools.